Financial Astrology: An Empirical Study of the Western Horoscopes on Worldwide Equities Markets - Lee, Loo Ee (2007)
Astral science is the most ancient and a wonder in science, has purported to have established the truth that there is a strong connecting link between human events and planetary configurations. The rise and fall of stock markets may be traced to certain planetary positions and aspects which are periodic. Wars, revolutions, political changes, new treaties of commerce, bad or good harvests may occur to decrease or increase the activity of trade. This could be witnessed by the past World War I and II in the early and middle of nineties. Although from the planetary configurations could result the stock market increase or decrease in value, the degree of rise or fall of the respective market cannot be definitely estimated. (http://www.howisyourdaytoday.com)